Characterization of platelet dysfunction after trauma - Kutcher, Matthew E (2012)
BACKGROUND: The increased morbidity and mortality associated with coagulopathy and thrombocytopenia after trauma are well-described. However, few studies have assessed platelet function after injury. METHODS: Blood samples were prospectively collected from 101 critically-injured trauma patients on arrival to the emergency department and serially after admission to a Level I urban trauma ICU from November 2010 to October 2011, and functionally assayed for responsiveness to adenosine diphosphate, thrombin receptor-activating peptide (TRAP), arachidonic acid (AA), and collagen using multiple electrode impedance aggregometry. RESULTS: Of 101 enrolled patients, 46 (45.5%) had below-normal platelet response to at least one agonist (‘platelet hypofunction’) on admission, and 92 patients (91.1%) had platelet hypofunction at some time during their ICU stay. Admission platelet hypofunction was associated with low Glasgow coma score (GCS) and a nearly 10-fold higher early mortality. Logistic regression identified admission GCS (odds ratio 0.819, p=0.008) and base deficit (odds ratio 0.872, p=0.033) as independent predictors of platelet hypofunction. Admission AA and collagen responsiveness were significantly lower in patients who died (p<0.01), while admission platelet counts were similar (p=0.278); Cox regression confirmed TRAP, AA, and collagen responsiveness as independent predictors of in-hospital mortality (p<0.05). Receiver operator characteristic analysis identified admission AA and collagen responsiveness as negative predictors of both 24-hour (AA AUC: 0.874, collagen AUC: 0.904) and in-hospital mortality (AA AUC: 0.769, collagen AUC: 0.717). CONCLUSIONS: In this prognostic study, we identify clinically significant platelet dysfunction after trauma in the presence of an otherwise reassuring platelet count and standard clotting studies, with profound implications for mortality. Multiple electrode impedance aggregometry reliably identifies this dysfunction in injured patients, and admission arachidonic acid and collagen responsiveness are sensitive and specific independent predictors of both early and late mortality. LEVEL OF EVIDENCE: Level I